Outcome of Humeral Shaft Fracture Treated with Anteromedial Plating through an Anterolateral Approach - Nepal, Prabin; Shrestha, Sailendra Kumar Duwal; Karki, Umash; Karki, Netra Bahadur; Shrestha, Kumar (Annapurna Journal of Health Sciences, 2023)
Introduction: Humerus shaft fracture is a common injury representing 1.2-3% of all fractures. It can be managed both conservatively and operatively with various modalities. Among operative, plate osteosynthesis is the most widely accepted method of treatment when conservative treatment is not adequate to achieve union with good functional outcome. Anteromedial plating through anterolateral approach is a safe and reliable approach in plate osteosynthesis. Methods: A prospective study was conducted in the Department of orthopaedics, Nepal APF hospital, Kathmandu from 2015 February to 2020 February. Fortyfour patients who underwent anteromedial plating for humeral shaft fracture were included in the study. Patients were evaluated for functional recovery and progress of fracture healing. Rodrigeuz-Merchan criteria was used to grade the functional outcome. Results: A total of 44 patients were included in the study with mean age of 36. There were 31 males and 13 females. The majority of patients 31 (70.45%) sustained injury due to road traffic accident followed by fall from height 11 (25%) and direct injury 2(4.55%). The most common fracture pattern was AO /OTA Type A. The mean duration of surgery was 60±15min. Fracture union occurred in less than 4 months in 36 patients (81.81%). Rodriguez Merchan criteria showed majority of the patients had excellent 23(52.27%) and good 15 (34.1%) functional outcomes. Conclusion: Anteromedial plating provides a safe form of fixation of humeral shaft fracture. It has benefit of supine positioning of the patient during operation with good union rate, less fixation time, lesser complications leading to better functional outcome.